Prevalence of bacterial contamination on seafoods products collected from traditional fish market in Bali Province during 2023: Prevalensi kontaminasi bakteri pada produk hasil ikan laut yang dikumpulkan dari pasar ikan tradisional di Provinsi Bali selama tahun 2023 - Sudaryatma, Putu Eka; Wiradana, Putu Angga; Razaq, Imanuddin; Sunarsih, Ni Luh; Jatmiko, Aris; Permatasari, Anak Agung Ayu Putri; Sari, Ni Kadek Yunita; Widhiantara, I Gede; Sandhika, I Made Gde Sudyadnyana; Rosiana, I Wayan (Jurnal Pengolahan Hasil Perikanan Indonesia, 2025)
Seafood provides essential nutrients beneficial for human health; however, it is highly vulnerable to harmful bacterial infections that pose significant public health risks. This research seeks to assess the prevalence of five categories of seafood obtained from various traditional fish markets in Bali Province. A total of 108 tuna samples, 78 pelagic fish samples, 37 cephalopod samples, 14 sardine samples, and 53 demersal fish samples were collected from various traditional markets in Bali Province. This research evaluated the prevalence of E. coli, coliforms, Salmonella, V. cholerae, and V. parahaemolyticus. The study revealed that the highest prevalence of E. coli, coliform, and V. parahaemolyticus contamination in tuna samples was 95 (87%), 95 (87%), and 103 (95%), respectively. The study indicated that E. coli and coliforms were present in 73 of the 78 pelagic fish samples, representing 93% contamination. Sardine samples exhibited the lowest prevalence of bacteria. All seafood samples, however, tested negative for Salmonella and V. cholera. PCR products from E. coli and V. parahaemolyticus isolates were effectively amplified for the target genes utilized in this study. Local seafood markets should adopt appropriate handling and storage practices to enhance seafood quality. This study emphasizes the significant presence of E. coli, coliforms, and V. parahaemolyticus in seafood, along with the potential health risks posed by specific strains and their antibiotic resistance.